In the woods - Elliott, David, 1947- (Candlewick Press, 2020)
The animals in the dark woods are secretive, their inner lives a mystery. The stealthy bobcat, the inquisitive raccoon, and the dignified bear waking up from his winter nap are just a few of the glorious animals featured in this collection of poems and woodland scenes.--page [2] of cover.